EVALUASI DOSIS ASAM VALPROAT PADA PASIEN EPILEPSI ANAK DI BANGSAL RAWAT INAP ANAK RSUP DR. SARDJITO YOGYAKARTA - , Masita Wulandari S; , Prof. Dr. Djoko Wahyono, SU., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Epilepsy is a neurological condition characterized by recurrent seizures recurrence. Most cases of epilepsy in children at age 1-6 years (46,5%), 6-10 years (29,1%), 10-18 years (16,28%) and 0-1 years (8,14%).The high prevalence of epilepsy children can lead to many use of antiepileptic drugs, is one of the antiepileptic drug valproic acid. Valproic acid is a drug with a narrow therapeutic index therapeutic range of 50-100 mg/L. The use of children aged < 2 years are at greater risk of toxic to the pancreas and liver. That requires monitoring and dose adjustments to prevent toxic effects. Monitoring TDM (Therapeutic Drug Monitoring) can be done through a review of pharmacokinetics to estimate the therapeutic dose levels of the drug by the patient. So known drug levels in the blood and associatedwith therapeutic results obtained. This study is a retrospective study with a descriptive analysis of the observational design. Research subject is a child epilepsy patients with valproic acid monotherapy period January 2009 - December 2013 aged 2-14 years, men and women who are hospitalized. The results observed therapy is seizure-free duration (< 6 months and â¥6 months). The results of this study were 24 patients (48%) corresponding to the therapeutic range (50-100 mg/L) and 26 patients (52%) were not in accordance with the therapeutic range (<50 mg/L or >100 mg/L). Clinical outcomes was assessed based on the duration of seizure free patients showed 37 patients (74%) gave good outcome and 13 patients (26%) gave a por outcome.